Creation of mass dimension one fermionic particles in asymptotically expanding universe - Pereira, S. H. [UNESP]; Lima, Rodrigo C. [UNESP] (World Scientific Publishing, 2017)
In the present work we study the process of particle creation for mass dimension one fermionic fields (sometimes named Elko) as a consequence of expansion of the universe. We study the effect driven by an expanding background that is asymptotically Minkowski in the past and future. The differential equation that governs the time mode function is obtained for the conformal coupling case and, although its solution is nonanalytic, within an approximation that preserves the characteristics of the terms that break analyticity, analytic solutions are obtained. Thus, by means of Bogolyubov transformations technique, the number density of particles created is obtained, which can be compared to exact solutions already present in literature for scalar and Dirac particles. The spectrum of the created particles was obtained and it was found that it is a generalization of the scalar field case, which converges to the scalar field one when the specific terms concerning the Elko field are dropped out. We also found that lighter Elko particles are created in larger quantities than the Dirac fermionic particles. By considering the Elko particles as candidate to the dark matter in the universe, such result shows that there are more light dark matter (Elko) particles created by the gravitational effects in the universe than baryonic (fermionic) matter, in agreement to the standard model.
Keywords: Elko field; Mass dimension one fermion; particle creation